Effect of Memantine on Cough Reflex Sensitivity: Translational Studies in Guinea Pigs and Humans - Dicpinigaitis, Peter V.; Canning, Brendan J.; Garner, Rachel; Paterson, Blake (The Journal of pharmacology and experimental therapeutics, 2015)
Cough is the most common complaint for which outpatients in the United States seek medical attention, and yet available therapeutic options for cough lack proven efficacy and are further limited by safety and abuse liabilities. Thus, safe and effective cough suppressants are needed. Recent preclinical studies described the antitussive effects of memantine, an N-methyl-d-aspartate receptor channel blocker used in the treatment of Alzheimer's disease. The goals of the present study were to compare the antitussive effects of memantine, dextromethorphan, and codeine in guinea pigs; to relate the dose-dependent actions of memantine in these studies to peak plasma concentrations achieved following oral administration; and to provide the first ever evaluation of the antitussive effect of memantine in humans. In guinea pigs, memantine and codeine were comparable in efficacy and potency but both were superior to dextromethorphan in the citric acid cough challenge model. The pharmacokinetic analyses suggest that memantine was active in guinea pigs at micromolar plasma concentrations. Subsequently, 14 healthy volunteers as well as 14 otherwise healthy adults with acute viral upper respiratory tract infection (URI) underwent capsaicin cough challenges 6 hours after ingestion of 20 mg memantine and matched placebo in a randomized, double-blind, crossover fashion. In healthy volunteers, memantine significantly inhibited cough reflex sensitivity (P = 0.034). In subjects with URI, responsiveness to capsaicin was markedly increased, and in these patients, the inhibition of cough reflex sensitivity by memantine relative to placebo did not reach statistical significance (P = 0.088). These data support further research to investigate the potential of memantine as a clinically useful antitussive.